2015
DOI: 10.1007/s11663-015-0364-4
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Alloying Elements Ti, Nb, Mn, Ni, and Cr in Double-Stabilized Ferritic Stainless Steel Process Sample Using an Electrolytic Extraction Method and Separate Analysis of Inclusions

Abstract: TEIJA SIPOLA, TUOMAS ALATARVAS, EETU-PEKKA HEIKKINEN, and TIMO FABRITIUS Chromium, nickel, and manganese are common alloying elements in stainless steels. Additionally, titanium and niobium are added as microalloying elements to certain stainless steel grades. A double-stabilized stainless steel sample was dissolved in electrolyte using an electrolytic extraction method. Inclusions were separated from the electrolyte with vacuum filtration and put through a separate elemental analysis. Steel-soluble alloying e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…An inclusion size distribution and chemical composition has been determined in the previous article 15) on the stainless steel sample 1 and it was concluded that a clear majority of the inclusions were Ti and Nb containing inclusions of 1-3 μm in size.…”
Section: Examination Of Inclusionsmentioning
confidence: 99%
See 2 more Smart Citations
“…An inclusion size distribution and chemical composition has been determined in the previous article 15) on the stainless steel sample 1 and it was concluded that a clear majority of the inclusions were Ti and Nb containing inclusions of 1-3 μm in size.…”
Section: Examination Of Inclusionsmentioning
confidence: 99%
“…14) In the previous study, microalloying elements titanium, niobium, nickel, manganese, and chromium were determined from a stainless steel matrix and inclusions using the method of electrolytic extraction and elemental analysis. 15) In this study, alloying elements and impurities with even smaller contents were determined from steel matrix and inclusions from a stainless steel process sample. An electrolytic extraction method is used to separate stainless steel matrix and inclusions in two common electrolytes in inclusions studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the smallest inclusions and precipitates in steel C were also examined by using electrolytic extraction as described in detail in Ref. [25]. Briefly, this technique uses multistep extraction and filtration based on dissolution of the matrix in an HCl electrolyte.…”
Section: Fig 1 -Schematic Process For Sem-eds Particle Analysismentioning
confidence: 99%
“…Steel cleanliness is governed by the amount, size distribution, morphology and composition of the non-metallic inclusions that originate during different stages of processing including solidification, [6][7][8][9] and is one of the main criteria that can restrict the performance of 347 stainless steel. For example, both formability and fatigue life are strongly affected by the presence of sulphides and oxides.…”
Section: Introductionmentioning
confidence: 99%